IDENTIFIKASI SENYAWA TOKSIK EKSTRAK KLOROFORM KULIT BIJI NYAMPLUNG (Calophyllum inophyllum L.) - Sri Rahayu Santi; I Wayan Suirta; Kadek Agus Andika Pratama (Jurnal Kimia (Journal of Chemistry), 2012)
Identification  of active toxic compounds from chloroform extract Nyamplung skin bean (Calophyllum inophyllum L) have been conducted. As much as 2,85 g n-hexane extract, 7,42 chloroform extract, and 4,71 water extract were resulted from 1 kg Nyamplung skin bean. Separation of  2 g  chloroform extract  using column chromatography (stationary phase: silica gel 60 and mobile phase chloroform-methanol 9,5:0,5) resulted  in four fraction with yellowish fraction (0,473 g) as the most toxic fraction (LC50 8,241 ppm). Identification using GC-MS showed that the isolate was hexadecanoic acid (21,02%), 8-octadecenoic acid (59,55%), and oktadecanoic acid(19,43%).